Do Boys and Girls Display Different Levels of Depression in Response to Mobile Phone Addiction? Examining the Longitudinal Effects of Four Types of Mobile Phone Addiction - Xu X; Li H; Bai R; Liu Q (Psychology Research and Behavior Management)
Xiaopan Xu,1 Hongwei Li,2 Ru Bai,3 Qingqi Liu4,5 1Institute for Public Policy and Social Management Innovation, College of Political Science and Public Administration, Henan Normal University, Xinxiang, People’s Republic of China; 2School of History and Culture, Henan Normal University, Xinxiang, People’s Republic of China; 3School of Applied Engineering, Henan University of Science and Technology, Luoyang, People’s Republic of China; 4Department of Psychology, Faculty of Arts and Sciences, Beijing Normal University at Zhuhai, Zhuhai, People’s Republic of China; 5School of Education, Guangzhou University, Guangzhou, People’s Republic of ChinaCorrespondence: Hongwei Li, Henan Normal University, Xinxiang, Henan Province, People’s Republic of China, Tel +86-18039107193, Fax +0373-3326384, Email 2013042@htu.edu.cnPurpose: Prior research has indicated that mobile phone addiction (MPA) significantly contributes to depression. However, there is a research gap in exploring the distinct impacts of various types of MPA on depression, along with the potential moderating effect of gender. The current study investigated whether the relationship between MPA and depression varies depending on the types of MPA and gender.Methods: A one-year longitudinal study was undertaken at two high schools in Central China. Data was gathered at two time points (Time 1/T1 and Time 2/T2) with a one-year gap between assessments. A total of 480 adolescents, aged 12 to 19 years old, completed all questionnaires assessing four types of mobile phone addiction at T1, as well as depression at T1 and T2.Results: The findings demonstrated significant positive associations between all four types of MPA at T1 and depression at T2. Additionally, gender was found to moderate the associations between three types of MPA and depression. Specifically, among girls, T1 social media addiction had a stronger predictive effect on T2 depression compared to boys. Conversely, among boys, T1 game addiction had a more pronounced predictive effect on T2 depression, which was less significant among girls. Moreover, in boys, T1 short-form video addiction had a noteworthy predictive effect on T2 depression, but this effect was not significant in girls. However, it is worth noting that T1 information acquisition addiction had a significant predictive effect on T2 depression in both boys and girls, with no noticeable gender difference.Conclusion: The current study has enhanced our understanding of the impact of MPA on mental health by examining the correlation between different types of MPA and depression across genders. The findings provide valuable insights for reducing depression among adolescents of different genders by considering their mobile phone usage patterns.Keywords: mobile phone addiction, depression, gender, moderating effects, adolescents